Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G.; Atkinson, R.; Rokas, A.; Csoka, G.; Nieves-Aldrey, J. L.; Csoka, G.; Nieves-Aldrey, J. L. (MOLECULAR ECOLOGY, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cem's from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south-west France are allied to Spain, while ail remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south-west France is marked by abrupt transitions in the frequency of refuge-specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north-west France, none were detected where the two lifecycles meet in south-western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow and limited to regions where Q. cem's and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.
From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL accession-num: 11298986
Keywords: Alleles; Andricus; Animals; Base Sequence; Cellulose Acetate; Cytochrome b Group; Cytochrome b Group: chemistry; Cytochrome b Group: genetics; DNA; Electrophoresis; Environment; EUROPE; Evolution; Female; gallwasp; Genetic Variation; Genetic Variation: physiology; glacial refugia; host race; Hymenoptera; Hymenoptera: genetics; Hymenoptera: growth & development; Hymenoptera: physiology; invasion; Life Cycle Stages; Mitochondrial; Mitochondrial: chemistry; Mitochondrial: isolation & purification; Molecular; Molecular Sequence Data; Parthenogenesis; phylogeny; Polymerase Chain Reaction; range expansion; Sequence Alignment; Sequence Analysis

Anaphylactic reaction to ingestion of Quercus ilex acorn nut - Vega; DomÍnguez; Cosmes; MartÍnez; BartolomÉ, B.; Palacios; Vega, a; Domínguez, C.; Cosmes, P.; Martínez, a; BartolomÉ, B.; Martínez, J.; et al. (Clinical & Experimental Allergy, 1998)
Background A patient experienced an anaphylactic reaction after eating acorn nuts, fruit of the holm oak (Quercus ilex), one of the most abundant trees in Spain. Several urticaria episodes upon ingestion of peanuts were also referred. Objective To assess the hypersensitivity reaction to acorn and to characterize the allergenic proteins involved. Methods Cutaneous tests were performed using the skin-prick technique, using a large variety of grass, tree and weed pollens as well as fresh nuts and nut extracts. Specific IgE determination was assessed by RAST. IgE binding bands were determined by SDS-PAGE immunoblotting. Results Skin-prick tests were strongly positive with acorn and peanut. Olea europaea, Quercus alba, Quercus ilex and grass pollens also elicited a weal higher than negative control. Patient serum had measurable levels of IgE antibodies especially to acorn, peanut and grass pollens. Only one protein band, of 17.9 kDa molecular mass, showed IgE-binding properties in the acorn extract. The possible homology of this strong allergenic protein with the group 1 tree pollen allergens was evidenced by the partial inhibition of the western blot with Bet v 1. Conclusions We present a case of anaphylaxis to acorn ingestion as demonstrated by in vivo and in vitro results. A 17.9 kDa IgE-binding band, showing some homology to group 1 pollen tree allergens, was recognized by patient serum.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd, UK accession-num: 9677139
Keywords: acorn allergens; Anaphylaxis; Anaphylaxis: drug therapy; Anaphylaxis: etiology; Bet v 1; Cross Reactions; Electrophoresis; Food Hypersensitivity; Food Hypersensitivity: drug therapy; Food Hypersensitivity: etiology; Humans; Immunoblotting; Immunoglobulin E; Immunoglobulin E: blood; Male; Middle Aged; nut allergy; Nuts; Nuts: adverse effects; Nuts: immunology; Polyacrylamide Gel; Quercus ilex allergy; Radioallergosorbent Test; Skin Tests